The Use of Lapbook Learning Media in Science Subjects to Increase Motivation and Creativity of Students of SD N Genengsari 03 Polokarto - Rika Kurnia; Para Mitta Purbosari; Dwi Hastuti (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
Learning media plays an important role in creating an effective and efficient learning process. However, there are still teachers who are not aware of the benefits of learning media, so that the learning process becomes less interesting. Observations in Class IV of SD N Genengsari 03 Polokarto showed that students' creativity and interest in learning were still low, with most students preferring a visual learning style. One of the appropriate media is a lapbook, which is a creative portfolio in the form of a collection of mini-books and folded paper in a colored cardboard folder. The study used the Kurt Lewin class model with two cycles. The results showed a significant increase in students' creativity and interest in learning after using lapbooks. In the pre-action, the aspects of originality and visual design were still lacking (100%), but in Cycle II it increased with 33.33% of students in originality, 37.04% visual design, 44.44% relatedness of ideas, and 48.15% problem-solving ability. Student enthusiasm also increased from 0% to 48.15%. In addition, learning interest increased with aspects of material interest from 0% to 40.74%, active involvement 55.56%, attention 62.96%, and pleasure 59.26% in Cycle II. In conclusion, lapbook media is effective in increasing students' creativity and interest in learning significantly and gradually.